2021
DOI: 10.1016/s1473-3099(20)30928-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic signatures for diagnosing tuberculosis in clinical practice: a prospective, multicentre cohort study

Abstract: Summary Background Blood transcriptomic signatures for diagnosis of tuberculosis have shown promise in case-control studies, but none have been prospectively designed or validated in adults presenting with the full clinical spectrum of suspected tuberculosis, including extrapulmonary tuberculosis and common differential diagnoses that clinically resemble tuberculosis. We aimed to evaluate the diagnostic accuracy of transcriptomic signatures in patients presenting with clinically suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“… Triage Collection method and not a test itself - Studies are few and heterogenous, no pooled performance estimates exist - Ultra applied to a single swab had a sensitivity of 88% in outpatients 41 but only 43% sensitivity when used for active case finding in a prison 40 - TB-LAMP 42 applied to oral swabs had sensitivities ranging from 33-50% - FLOQSwabs (Copan Italia) preferred 41 - Self-swabbing, comparable to health worker-administered swabs for other pathogens 44 , appears feasible - Potential for paediatric TB 43 - Insufficient Mtb may be recovered from swabs in patients with low sputum bacillary load 40 - Performance of novel assays (e.g., next-generation LAM and NAATs unknown) may overcome sensitivity limitations associated - Optimal number of swabs, swab design, and the processing method are under evaluation and may improve the release of material from swabs -No tests purpose-built for tongue swabs yet exist Blood Host transcriptome mRNA blood signatures associated with the immune system's response to Mtb have shown promise for diagnosis. 68 Triage Xpert Host Response (Cepheid) - A multicentre study showed 90% sensitivity and 86% specificity 64 -Other studies have shown lower specificities (26% 101 , 53% 102 ) at >90% sensitivity - Limited data with small numbers of cases, however, multicentre studies are emerging - Xpert HR has the most data available - RNA is labile and, for Xpert HR, time from blood collection to testing must be <30 min and stabilisation agents may be required - Cost unclear, but likely high - Potential utility treatment response monitoring, management of diseases other than TB (signature-positive patients without TB could have other infections 95 ), and false-positive TB PCR results 65 , which are frequent in people with previous TB 68 , 84 , 103 - Signatures (including Sweeney3 in Xpert HR) measured using ultra-sensitive methods (sequencing, Nanostring) 68 struggle to meet WHO TPPs 65 , 66 ...…”
Section: Overview Of Diagnostic Technologies and Tests By Specimen Typementioning
confidence: 99%
“… Triage Collection method and not a test itself - Studies are few and heterogenous, no pooled performance estimates exist - Ultra applied to a single swab had a sensitivity of 88% in outpatients 41 but only 43% sensitivity when used for active case finding in a prison 40 - TB-LAMP 42 applied to oral swabs had sensitivities ranging from 33-50% - FLOQSwabs (Copan Italia) preferred 41 - Self-swabbing, comparable to health worker-administered swabs for other pathogens 44 , appears feasible - Potential for paediatric TB 43 - Insufficient Mtb may be recovered from swabs in patients with low sputum bacillary load 40 - Performance of novel assays (e.g., next-generation LAM and NAATs unknown) may overcome sensitivity limitations associated - Optimal number of swabs, swab design, and the processing method are under evaluation and may improve the release of material from swabs -No tests purpose-built for tongue swabs yet exist Blood Host transcriptome mRNA blood signatures associated with the immune system's response to Mtb have shown promise for diagnosis. 68 Triage Xpert Host Response (Cepheid) - A multicentre study showed 90% sensitivity and 86% specificity 64 -Other studies have shown lower specificities (26% 101 , 53% 102 ) at >90% sensitivity - Limited data with small numbers of cases, however, multicentre studies are emerging - Xpert HR has the most data available - RNA is labile and, for Xpert HR, time from blood collection to testing must be <30 min and stabilisation agents may be required - Cost unclear, but likely high - Potential utility treatment response monitoring, management of diseases other than TB (signature-positive patients without TB could have other infections 95 ), and false-positive TB PCR results 65 , which are frequent in people with previous TB 68 , 84 , 103 - Signatures (including Sweeney3 in Xpert HR) measured using ultra-sensitive methods (sequencing, Nanostring) 68 struggle to meet WHO TPPs 65 , 66 ...…”
Section: Overview Of Diagnostic Technologies and Tests By Specimen Typementioning
confidence: 99%
“…Furthermore various transcriptomic signatures that distinguish between latent and active disease in high-incidence settings have been reported [20,21]. Recently however in a whole blood microarray analysis of TB patients in a low-incidence setting, transcriptomic signatures were not found to be sufficiently sensitive or specific to diagnose TB [22]. Additionally, a review has found that the diagnostic accuracy of previously published transcriptomic signatures for TB was lower than reported [117].…”
Section: Distinguishing Ltbi From Active Tb Diseasementioning
confidence: 99%
“…In an adult population in a high-incidence setting, a 44-transcript signature was used to calculate a disease risk score for patients which was found to differentiate between active TB and other diseases with a sensitivity of 93% and specificity of 88% [21]. In a prospective study from a low-incidence setting, the highest performing transcriptomic signature indicative of active TB had both a sensitivity and specificity of 77%, which was insufficient to meet World Health Organisation (WHO) diagnostic cut-offs for non-sputum tests for smear-negative TB [22].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Jacobsen et al, 2007;Mistry et al, 2007;Berry et al, 2010;Maertzdorf et al, 2011a,b;Anderson et al, 2014;Cai et al, 2014;Zak et al, 2016;Singhania et al, 2018;Estévez et al, 2020 • Biomarkers that differentiate TB from other infectious diseases. Berry et al, 2010;Maertzdorf et al, 2012;Bloom et al, 2013;Kaforou et al, 2013;Anderson et al, 2014;Hoang et al, 2021 • Biomarkers for extrapulmonary TB.…”
Section: Weiner Et Al 2020mentioning
confidence: 99%
“…The scientific community has made efforts in discriminating the TB gene signature from extrapulmonary TB ( Roe et al, 2016 ) and other diseases ( Berry et al, 2010 ; Maertzdorf et al, 2012 ; Bloom et al, 2013 ), specially other pulmonary diseases or co-infecting diseases that are highly prevalent in TB endemic areas. Multicenter studies ( Kaforou et al, 2013 ; Anderson et al, 2014 ; Hoang et al, 2021 ) included a superior number of patients suffering from TB and other diseases, including HIV-coinfection.…”
Section: Transcriptomics Applied To Tuberculosis Researchmentioning
confidence: 99%